PENGARUH CASH RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURN OVER DAN PERTUMBUHAN PENJUALAN TERHADAP RETUREN ON EQUITY (Studi Empiris Pada Perusahaan Sub Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2022) - Adzhari, Putri; Oktaviani, Retno Fuji (Yayasan Nuraini Ibrahim Mandiri, 2024)
This study aims to analyze Cash Ratio, Debt to Equity Ratio, Total Asset Turn Over and Sales Growth on Return On Equity in Pharmaceutical Sub-Sector Companies Listed on the Indonesia Stock Exchange for the period 2018-2022. This research is a quantitative study using purpose sampling technique in determining the sample, and obtained 11 companies from 12 companies. The analysis model used in this research is multiple linear regression models. The results of this study indicate that Cash Ratio, Debt to Equity Ratio, and Total Asset Turn Over have a significant effect on Return On Equity, while Sales Growth has no effect on Return On Equity.